Activation of the Calcium-Sensing Receptor Corrects the Impaired Mitochondrial Energy Status Observed in Renal Polycystin-1 Knockdown Cells Modeling Autosomal Dominant Polycystic Kidney Disease - Di Mise, Annarita; Ranieri, Marianna; Centrone, Mariangela; Venneri, Maria; Tamma, Grazia; Valenti, Daniela; Valenti, Giovanna (Frontiers in Molecular Biosciences, 2018)
Autosomal Dominant Polycistic kidney Disease (ADPKD) is a renal channelopathy due to loss-of-function mutations in the PKD1 or PKD2 genes, encoding polycystin-1 (PC1) or polycystin-2 (PC2) respectively. PC1 is a large protein found predominantly on the plasma membrane where interacts with different proteins, including PC2. PC2 is a smaller integral membrane protein also expressed in intracellular organelles, acting as a non-selective cation channel permeable to calcium. Both PC1 and PC2 are also localized to the primary cilium of renal epithelial cells serving as mechanosensor that controls calcium influx through the plasma membrane and regulates intracellular calcium release from the endoplasmic reticulum. The mechanisms by which PC1/2 dysfunction leads to ADPKD needs still to be clarified. We have recently reported that selective Calcium-Sensing Receptor (CaSR) activation in human conditionally immortalized Proximal Tubular Epithelial cells deficient for PC1 (ciPTEC-PC1KD), deriving from urine sediments reduces intracellular cAMP and mTOR activity, and increases intracellular calcium reversing the principal ADPKD dysregulations. Reduced cellular free calcium found in ADPKD can, on the other hand, affect mitochondrial function and ATP production and, interestingly, a relationship between mitochondria and renal polycystic diseases have been suggested. By using ciPTEC-PC1KD as experimental tool modeling of ADPKD, we show here that, compared with wild type cells, ciPTEC-PC1KD have significantly lower mitochondrial calcium levels associated with a severe deficit in mitochondrial ATP production, secondary to a multilevel impairment of oxidative phosphorylation. Notably, selective CaSR activation with the calcimimetic NPS-R568 increases mitochondrial calcium content close to the levels found in resting wild type cells, and fully recovers the cell energy deficit associated to the PC1 channel disruption. Treatment of ciPTEC-PC1KD with 2-APB, an IP3R inhibitor, prevented the rescue of bioenergetics deficit induced by CaSR activation supporting a critical role of IP3Rs in driving ER-to-mitochondria Ca2+ shuttle. Together these data indicate that, besides reversing the principal dysregulations considered the most proximal events in ADPKD pathogenesis, selective CaSR activation in PKD1 deficient cells restores altered mitochondrial function that, in ADPKD, is known to facilitate cyst formation. These findings identify CaSR as a potential therapeutic target.